PSYCHOLOGICAL DISTRESS AMONG CAREGIVERS OF PATIENTS WITH SCHIZOPHRENIA - Shah, Syed Tahir H; Sultan, Syed Mohammad; Faisal, Mohammad; Faisal, Mohammad; Irfan, Muhammad (Journal of Ayub Medical College Abbottabad, 2013)
Background: Schizophrenia is a devastating disorder not only for the patients but also for their caregivers. The caregivers of the patients suffer from psychological distress but receive minimum support from psychiatric services. Objectives were to assess the stress level in caregivers of patients with schizophrenia and to determine the association of stress with demographic variables of caregivers. Methods: It was a descriptive hospital based study carried out in Psychiatry Department of Khyber Teaching Hospital, Peshawar. Fifty caregivers were included in the study during a period of one year. Socio-demographic variables were recorded on specially designed pro forma. Stress level was assessed by using Self Report Questionnaire (SRQ-20) with a cut off score of 9 being taken as stressed. Results: Mean age of the caregivers was 45.44±14.25 years. Forty-two (84%) caregivers were males and 8 (16%) were females. Twenty-eight (56%) were uneducated, 16 (32%) had Primary education, 4 (8%) were matriculates and 2 (4%) graduates. Thirty-four (68%) of the caregivers were married 8 (16%each unmarried and widows/widowers. Thirty-two (64%) were unemployed and 18 (36%) were employed. Two (4%) had been providing care for less than 6 months, 4 (8%) for less than 12 months, 10 (20%) for less than 18 months, 2 (4%) for less than 24 months and 32 (64%) for more than 24 months. 22 (44%) were parents, 14 (28%) were siblings, 2 (4%) were children of the patients. Thirty-six (72%) caregivers were having score of more than 9 on SRQ-20. Stress showed a statistically significant association only with age (p-value <0.004). Conclusion: Psychological distress is present in majority of the caregivers of patients with schizophrenia. There is statistically significant association between age of the caregiver and psychological distress, while gender, educational status, marital status, occupational status, duration of care and relation with the patient are not associated with psychological distress. Keywords: Psychological distress, caregivers, schizophrenia, Peshawar